Effect of Different Levofloxacin Doses on QTc Interval Prolongation in Multidrug-Resistant Tuberculosis Patients Treated with the 9-Month All-Oral Regimen - Soedarsono, Soedarsono; Rampengan, Vicky Reinold Christofel; Agustiyanto, Catur; Cho, Yong-Soon (Jurnal Respirasi, 2024)
Introduction: The World Health Organization (WHO) has recommended the 9-month all-oral regimen for multidrug-resistant tuberculosis (MDR-TB) treatment. This regimen is expected to increase the treatment success rate. Bedaquiline, levofloxacin, and clofazimine are QT-prolonging drugs included in the 9-month all-oral regimen. Bedaquiline and clofazimine are given at the same dose for all patients, while levofloxacine dose is given in 750 mg and 1,000 mg based on the body weight. This study analyzed the correlation between different levofloxacin doses and certain factors on QTc interval prolongation. Methods: This observational retrospective study used the medical records of MDR-TB patients who underwent the 9-month all-oral regimen. Electrocardiography (ECG) for QTc interval measurement was recorded at the baseline before and 2 weeks after treatment. The measured variables included patient demographic data, body mass index (BMI), electrolyte levels, and comorbidities. Results: Thirty MDR-TB patients were included in this study. Gender, diabetes mellitus (DM), and levofloxacin dose did not correlate with QTc interval prolongation at 2 weeks after drug administration (p-values of 0.558, 0.197, and 0.134, respectively). Age, potassium level, magnesium level, calcium level, and baseline QTc interval also did not correlate with QTc interval prolongation at 2 weeks after drug administration (p-values of 0.433, 0.479, 0.705, 0.746, and 0.333, respectively). Multivariate analysis showed that the risk factor associated with QTc interval prolongation at 2 weeks after drug administration was a BMI of 0.013. Conclusion: Different levofloxacin doses did not correlate with QTc interval prolongation in MDR-TB patients treated with the 9-month all-oral regimen. The incidence of QTc interval prolongation was significantly associated with the lower BMI level.